Imaging Identity: Media, memory and portraiture in the digital age - Hinkson, Melinda (ANU Press, 2016)
Imaging Identity presents potent reflections on the human condition through the prism of portraiture. Taking digital imaging technologies and the dynamic and precarious dimensions of contemporary identity as critical reference points, these essays consider why portraits continue to have such galvanising appeal and perform fundamental work across so many social settings. This multidisciplinary enquiry brings together artists, art historians, art theorists and anthropologists working with a variety of media. Authors look beyond conventional ideas of the portrait to the wider cultural contexts, governmental practices and intimate experiences that shape relationships between persons and pictures. Their shared purpose centres on a commitment to understanding the power of images to draw people into their worlds. Imaging Identity tracks a fundamental symbiosis - to grapple with the workings of images is to understand something vital of what it is to be human.